Current Issues in Public School Law - Julie Underwood O'Hara (Educational Considerations, 1984)
During the 1980s, educators will be forced to take on more responsibilities. Recent cases show the courts willing to abide by a "hands-off" policy as long as constitutional and/or statutory rights are not violated.